Neutrophil exhaustion and impaired functionality in psoriatic arthritis patients - Modestino, Luca; Tumminelli, Manuela; Mormile, Ilaria; Cristinziano, Leonardo; Ventrici, Annagioia; Trocchia, Marialuisa; Ferrara, Anne Lise; Palestra, Francesco; Loffredo, Stefania; Marone, Gianni; Rossi, Francesca Wanda; de Paulis, Amato; et al. (Frontiers in Immunology, 2024)
Background: Neutrophils (polymorphonuclear leukocytes, PMNs) are the most abundant subtype of white blood cells and are among the main actors in the inflammatory response. Psoriatic arthritis (PsA) is a chronic inflammatory disease affecting both the axial and peripheral joints. Typically associated with psoriasis, PsA can also affect multiple systems and organs, including the nails and entheses. Despite the involvement of PMNs in PsA, their specific role in the disease remains poorly understood. This study aimed to characterize the biological functions of PMNs and neutrophil-related mediators in PsA patients. Materials and Methods: 31 PsA patients and 22 healthy controls (HCs) were prospectively recruited. PMNs were isolated from peripheral blood and subjected to in vitro stimulation with lipopolysaccharide (LPS), N-Formylmethionyl-leucyl-phenylalanine (fMLP), tumor necrosis factor (TNF), phorbol 12-myristate 13-acetate (PMA), or control medium. Highly purified peripheral blood PMNs (>99%) were evaluated for activation status, reactive oxygen species (ROS) production, phagocytic activity, granular enzyme and neutrophil extracellular traps (NETs) release. Serum levels of matrix metalloproteinase-9 (MMP-9), myeloperoxidase (MPO), TNF, interleukin 23 (IL-23), and interleukin 17 (IL-17) were measured by ELISA. Serum Citrullinated histone H3 (CitH3) was measured as a NET biomarker. Results: Activated PMNs from PsA patients displayed reduced activation, decreased ROS production, and impaired phagocytic activity upon stimulation with TNF, compared to HCs. PMNs from PsA patients also displayed reduced granular enzyme (MPO) and NET release. Serum analyses revealed elevated levels of MMP-9, MPO, TNF, IL-23, IL-17, and CitH3 in PsA patients compared to HCs. Serum CitH3 levels positively correlated with MPO and TNF concentrations, and IL-17 concentrations were positively correlated with IL-23 levels in PsA patients. These findings indicate that PMNs from PsA patients show reduced in vitro activation and function, and an increased presence of neutrophil-derived mediators (MMP-9, MPO, TNF, IL-23, IL-17, and CitH3) in their serum. Conclusions: Taken together, our findings suggest that PMNs from PsA patients exhibit an “exhausted” phenotype, highlighting their plasticity and multifaceted roles in PsA pathophysiology.